2015
DOI: 10.1152/ajpregu.00187.2015
|View full text |Cite
|
Sign up to set email alerts
|

The location of pacemakers in the uteri of pregnant guinea pigs and rats

Abstract: The pregnant uterus is a smooth muscle organ whose pattern of contraction is dictated by the propagation of electrical impulses. Such electrical activity may originate from one or more pacemakers, but the location of these sites has not yet been determined. To detect the location of the pacemaker in the gravid uterus, two approaches were used: 1) determine the site from where the contraction started using isolated uteri from the pregnant guinea pig, and videotape their contractions; and 2) record, in isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 40 publications
2
33
0
Order By: Relevance
“…In previous experiments on eight rats, with a total of 29 independent observations, we demonstrated that the majority of excitations recorded at the serosal surface originate from placental sites on the mesometrial border (Lammers et al . 2015).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In previous experiments on eight rats, with a total of 29 independent observations, we demonstrated that the majority of excitations recorded at the serosal surface originate from placental sites on the mesometrial border (Lammers et al . 2015).…”
Section: Resultsmentioning
confidence: 92%
“…To date, no pacemaker regions with specific anatomical features have been described in the mammalian uterus, which is perhaps surprising given that coordinated forceful contractions are essential to parturition. Multi‐electrode recordings of rat uteri demonstrated that potentials tend to initiate either at placental sites on the mesometrial border, or near the ovarian end (Lammers et al . 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In the available literature, there are few articles describing the contractility of the uterus and oviduct during early pregnancy (Lammers & van der Vusse, ; Lammers et al . ). This can be attributed to the methodological difficulties in achieving a successful AI with electrodes sutured on the oviducts.…”
Section: Discussionmentioning
confidence: 97%
“…; Lammers et al . ). Owing to the lack of information on the EMG activity of the oviducts in early pregnancy in sows, it is hard to relate the present results to the works of other authors (Lei et al .…”
Section: Discussionmentioning
confidence: 97%
“…However, it is still unclear whether there exists a specific pacemaker mechanism or a specific pacemaker area [11]. Except for some observations of contractile activity originating from specialized cells [12], most activities arise from any site throughout the myometrium [13, 14]. Among these sites, fundus is one possibility [15–17], hence we set the initiation of electrical activity to occur at the fundus in the simulations.…”
Section: Methodsmentioning
confidence: 99%